PVDF-TiO2 Hollow Fibre Membrane For Water Desalination - Elma, Muthia; Mahmud, Mahmud; Huda, Nurul; Assyaifi, Zaini L; Pratiwi, Elsa Nadia; Rezki, Mita Riani; Sari, Dewi Puspita; Rampun, Erdina Lulu Atika; Rahma, Aulia (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
The clean water crisis is increasing along with the increasing human population. Sea water is one of the largest water sources that can be utilized on the earth. However, the high salt concentration dissolved in seawater must be treated before it can use. Desalination is the directly technology for treating seawater with PVDF-TiO2 hollow fibre membrane via pervaporation process. The aim of this research was to determine the performance of PVDF-TiO2 hollow fibre membrane against variations in feed temperature in the artificial seawater pervaporation process. Method for fabrication membrane is using dry-wet spinning method. The result showed that the highest flux permeat occurred at feed temperature of 60ºC, namely 8.96 kg.m-2.h-1 with salt rejection > 92.86%. The result via SEM showed that of the membrane surface morphology, there is a white spot on the membrane surface is TiO2 because the dope solution is too thick. The PVDF-TiO2 hollow fiber membrane in this research is can be applied for seawater pervaporation.